1998
DOI: 10.1101/gad.12.14.2200
|View full text |Cite
|
Sign up to set email alerts
|

Igf2 imprinting does not require its own DNA methylation or H19 RNA

Abstract: Three models have been proposed to explain the imprinting of the mouse Igf2 gene on the maternal chromosome. We ruled out the importance of DNA methylation at Igf2 by showing that silencing of Igf2 accompanying the loss of DNA methylation could be overcome by a mutation at the neighboring H19 gene that activates Igf2. By replacing the H19 structural gene with a protein-coding gene, we have ruled out a role for H19 RNA in the imprinting of Igf2. This replacement resulted in sporadic activation of the H19 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 49 publications
(63 reference statements)
1
54
2
Order By: Relevance
“…Similar to the compensatory expression changes observed in our mutant mice, mutations that attenuated adult ␤-globin expression were accompanied by an increase in the expression of ⑀-globin (Foley and Engel 1992). Recent experiments by Jones and colleagues indicate that the competition by H19 and Igf2 promoters for the endoderm enhancers may not be mediated strictly by the promoters and DMD alone (Jones et al 1998a). In experiments in which the H19 transcriptional unit was replaced with the luciferase gene, luciferase was expressed at variable levels on the paternal allele, whereas the expression and imprinting of Igf2 was maintained at wild-type levels.…”
Section: Discussionsupporting
confidence: 54%
“…Similar to the compensatory expression changes observed in our mutant mice, mutations that attenuated adult ␤-globin expression were accompanied by an increase in the expression of ⑀-globin (Foley and Engel 1992). Recent experiments by Jones and colleagues indicate that the competition by H19 and Igf2 promoters for the endoderm enhancers may not be mediated strictly by the promoters and DMD alone (Jones et al 1998a). In experiments in which the H19 transcriptional unit was replaced with the luciferase gene, luciferase was expressed at variable levels on the paternal allele, whereas the expression and imprinting of Igf2 was maintained at wild-type levels.…”
Section: Discussionsupporting
confidence: 54%
“…Although the functional significance of the unusual maternal chromatin organization is unknown, this element upstream of the mouse H19 gene can act as a silencer in transgenic flies (34) and insulates the Igf2 gene from enhancers that are downstream of the H19 gene in the mouse (21,27,51,58). The boundary-insulator property of this element is observed on the maternal allele in the mouse, which is unmethylated in this region (53), as is the Drosophila genome (54).…”
Section: Discussionmentioning
confidence: 99%
“…This clearly demonstrated that sequences upstream and/or within H19 are also necessary for the paternal expression of these two neighboring imprinted genes (31). Two subsequent targeted deletions of H19 did not include upstream sequences and had only minor effects on Igf2 expression (27,42). Recently, a targeted deletion was performed in which a 1.6-kb element corresponding to the core region of paternal methylation upstream of H19 was deleted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the insulator sequence upstream of H19 comprises an "imprinting center" that regulates the reciprocal expression of H19 and Igf2. Although H19 is conserved among mammals and highly expressed in embryos, studies carried out over the last 15 yr indicate that the H19 transcript itself has no apparent role in the imprinted expression of its neighboring genes (Jones et al 1998) and is also not necessary for normal development in mice (Ripoche et al 1997). The chromosomal region containing H19 has also been associated with tumor suppressor activity, and the expression pattern of H19 RNA in several cancer cell types differs from neighboring nonmalignant cells (see "Regulatory RNAs Implicated in Complex Diseases: Dark Side of RNA" below).…”
Section: Igf2/h19 Locusmentioning
confidence: 99%